1999
DOI: 10.1002/(sici)1521-4141(199908)29:08<2385::aid-immu2385>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of TCR cross-reactivity using peptide libraries and protein databases

Abstract: A single T cell clone can be activated by many different peptides in the context of a particular HLA molecule. To quantify the number of peptides that can be recognized by a CD4+ T cell clone, we screened a one‐bead‐one‐peptide synthetic peptide library and a protein database for peptides that stimulate an HLA‐DR3‐restricted, human glutamic acid decarboxylase (GAD65)‐reactive CD4+ T cell clone. Both the library screening and the database analysis indicated that this T cell clone is able to recognize approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…A T-cell clone was isolated from a prediabetic subject 4 years prior to the clinical manifestation of diabetes [81]. This clone was used to define the antigen recognition pattern by screening a random synthetic peptide library dedicated to bind to the relevant HLA restriction element (HLA-DR3 in this case) [82,83,84]. A peptide of human cytomegalovirus major DNA-binding protein was identified that stimulated the autoreactive T-cell clone.…”
Section: Genetic and Environmental Factors Associated With T-cell Autmentioning
confidence: 99%
“…A T-cell clone was isolated from a prediabetic subject 4 years prior to the clinical manifestation of diabetes [81]. This clone was used to define the antigen recognition pattern by screening a random synthetic peptide library dedicated to bind to the relevant HLA restriction element (HLA-DR3 in this case) [82,83,84]. A peptide of human cytomegalovirus major DNA-binding protein was identified that stimulated the autoreactive T-cell clone.…”
Section: Genetic and Environmental Factors Associated With T-cell Autmentioning
confidence: 99%
“…Third, TCR multimers were used to screen for and identify syngeneic cross-reactive pMHCI ligands (Fig. 6); this approach eliminates the effects of adhesion/costimulatory molecular interactions that potentially confound cellular screening assays (47,48) and has recently been validated in class II-restricted systems (49). Surface plasmon resonance studies confirmed binding, with measured affinities for both HLA A2-Tel1p and HLA A2-HuD 87-95 lying at the lower end of the spectrum of previously defined TCR/pMHC interactions (22) (Fig.…”
Section: Functional Optimization Of Soluble Tcrsmentioning
confidence: 99%
“…All other peptides used in this study were synthesized on an automated multiple peptide synthesizer (Syroll, Multisyntech, Germany) and isolated as previously described (22). The purity of the peptides was determined by analytical reverse phase HPLC as previously described (22) and proved to be at least 70% (UV, 214 nm). The integrity of the peptides was determined by mass spectroscopy as previously described (22).…”
Section: Peptides and Mabsmentioning
confidence: 99%
“…The purity of the peptides was determined by analytical reverse phase HPLC as previously described (22) and proved to be at least 70% (UV, 214 nm). The integrity of the peptides was determined by mass spectroscopy as previously described (22). mAbs B8.11.2 specific for HLA-DR (23) and SPVL3 specific for HLA-DQ (24) were provided by Arend Mulder (Leiden University Medical Center, Leiden, The Netherlands).…”
Section: Peptides and Mabsmentioning
confidence: 99%